Preimplantation genetic testing for four families with severe combined immunodeficiency: Three unaffected livebirths - Lingyun Zhang; Lei Feng; Hao Shi; Wenbin Niu; Yanchi Wang; Bei Bu; Yidong Liu; Xiao Bao; Wenyan Song; Haixia Jin; Yingpu Sun (Orphanet Journal of Rare Diseases)
Abstract Purpose Severe combined immunodeficiency (SCID) is a set of rare monogenic inherited diseases that together represent the most severe form of the primary immunodeficiency disease phenotype. Preimplantation genetic testing for monogenic defects (PGT-M) is an effective reproductive technology strategy to prevent disease-causing gene mutations from being transmitted to offspring. The aim of this study was to report the use of PGT-M strategy based on karyomapping in four families to avoid the birth of SCID children. Methods Four couples underwent the PGT-M strategy due to SCID. The strategy of PGT-M started with a biopsy of the trophectoderm cells of embryos, and the whole genome was amplified by multiple replacement amplification (MDA). Then, the single nucleotide polymorphisms (SNPs) in the region upstream and downstream of the mutation site were subsequently identified via karyomapping, and the results were analyzed via SNPs linkage analysis. The aneuploids of the embryos were identified simultaneously. Finally, prenatal amniocentesis was used to verify the validity of the PGT-M results. Results We identified three novel variants (case1: IL2RG c.720_726delGAGCCAC; case 3: RAG2 c.770 C > T; and case 4: LIG4 c.1347 A > T). All four couples with SCID pathogenic gene mutations were subjected to karyomapping linkage analysis, and embryos with the pathogenic gene mutation were successfully identified. Euploid blastocysts without pathogenic alleles were transplanted, and healthy offspring were ultimately born. Prenatal diagnosis also confirmed the validity of our results. Conclusion This study revealed that karyomapping is an efficient approach for identifying SCID. Through PGT-M with karyomapping linkage analysis, healthy babies were born to families carrying mutations in the SCID pathogenic gene.